Project Performance Analysis Based on Earned Value Method on Infrastructure & Infrastructure Improvement of Yohanis Kapiyau Timika Airstrip - Nazaruddin, Nazaruddin; Djoko Nugroho, Laksono; Muhammadun, Haris (Pelopor Publikasi Akademika, 2025)
This study analyzes the performance of construction projects using the Earned Value Method (EVM) on the Infrastructure and Facilities Improvement Project at Yohanis Kapiyau Airbase in Timika. Utilizing key performance indicators such as Cost Variance (CV), Cost Performance Index (CPI), Schedule Variance (SV), and Schedule Performance Index (SPI), the research evaluates cost and time deviations to provide a comprehensive understanding of project performance. EVM offers precise insights into the project's current status, including estimates for total costs and completion timelines, which are critical for effective decision-making and ensuring adherence to project plans. The findings demonstrate that EVM is a reliable tool for accurately monitoring and managing construction projects, enabling stakeholders to identify inefficiencies and implement corrective measures in a timely manner. By providing an in-depth evaluation of cost efficiency and schedule performance, the study contributes to the broader application of EVM in enhancing construction project management. This research is expected to benefit academics by advancing theoretical knowledge, assist contractors in optimizing project execution, and inform public stakeholders on best practices for infrastructure development, ultimately contributing to more effective and efficient management of construction projects in Indonesia.